Suplementasi Kolin Klorida dalam Ransum untuk Meningkatkan Pertumbuhan Ayam Broiler - . Sumiati; W Hermana; A Afiati (Media Peternakan, 2006)
Cholin (B-hydroxyethyl-trimethylammonium hydroxide) is a constituent of phospholipids, can interfere the metabolism process that affects the growth. Sometimes cholin in a diet does not meet the animal requirement because of its low availability. The objective of the research was to study the effect of cholin chloride supplementation in the diets on broiler performance. A completely randomized design with 4 treatments and 4 replications were used in the experiment on broiler chicks reared up to 6 weeks of age. The treatment diets were R1 (control), R2 (R1 + 750 mg cholin chloride/kg diet), R3 (R1+ 1,500 mg cholin chloride/kg diet), R4 (R1+ 2,250 mg cholin chloride/kg diet). All of the prestarter diets (0-2 weeks of age) contained isocaloric (3,000 kcal ME/kg) and isoprotein (24.8% crude protein). The starter-finisher diet (2-6 weeks of age) contained 3,000 kcal ME/kg and 20% crude protein. Supplementation of 750 mg cholin chloride/kg diet (R2) increased (P < 0.01) body weight gain and final body weight. Supplementation of 1,500 mg cholin chloride/kg diet (R3) and 2,250 mg cholin chloride/kg diet decreased (P < 0.01) body weight gain, final body weight, as well as feed efficiency. It was concluded that supplementation of 750 mg cholin chloride/kg diet (containing 1,956 mg cholin/kg in prestarter diet and 1,791.3 mg cholin/kg in starter-finisher diet) yielded the best performance of the broilers. Key words : cholin chloride, broiler chickens, performance